The survey in the sociolinguistic research - Ramallo, Fernando; Lorenzo, Anxo M (Sociolinguistic Studies, 2002)
The aim of this paper is to present a description of the statistic survey since it constitutes an instrument traditionally related to the quantitative research and orientated towards social structure observation and analysis. The search for social object quantification has always been one of the most outstanding tendencies in the elaboration process of scientific knowledge, mainly from positivist theoretical perspectives. In some areas of sociolinguistic research the pertinence of surveys is obvious. After defining and contextualising surveys, we present a tipology and a section about the questionaire, which is the means of communication between the reasearcher and the analysed population. Then, we pay attention to the selection of observation unities and refer to the most important features of random and non-random samples. Finally, we offer a specific section about data treatment and we mention those most relevant theoretical aspects of descriptive and inferential statistics.